2003
DOI: 10.1038/sj.ejcn.1601522
|View full text |Cite
|
Sign up to set email alerts
|

Dairy products and colorectal cancer. A review of possible mechanisms and epidemiological evidence

Abstract: Objectives: This review provides an overview of the principal hypotheses and epidemiological evidence of the possible links between colorectal cancer and intake of milk and=or dairy products. Methods: The first section outlines the main hypotheses about the possible effect of calcium, vitamin D, fats and other milk components. The possible role of acid lactic bateria in fermented products is also discussed. The second section is a summary of the published epidemiological evidence. The results on milk, cheese a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
134
0
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(156 citation statements)
references
References 108 publications
9
134
0
10
Order By: Relevance
“…Another review revealed a consistent protective effect of dairy products on colorectal cancer occurrence in cohort studies but not in case-control studies. 6 The effect was not found in the CPSN cohort. 9 The analysis of the Pooling Project 12 (which did not include the CPSN cohort) revealed a lower risk of colorectal cancer in subjects who consumed over 250 g/day of dairy products than in those consuming under 70 g/day.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Another review revealed a consistent protective effect of dairy products on colorectal cancer occurrence in cohort studies but not in case-control studies. 6 The effect was not found in the CPSN cohort. 9 The analysis of the Pooling Project 12 (which did not include the CPSN cohort) revealed a lower risk of colorectal cancer in subjects who consumed over 250 g/day of dairy products than in those consuming under 70 g/day.…”
Section: Discussionmentioning
confidence: 86%
“…2,3,6 Newmark et al 1 first suggested in 1984 that ionised calcium might precipitate with secondary bile acids and fatty acids to generate insoluble soap, protecting the mucosa from their deleterious effect. Later, others 33 suggested that phosphorus might also be involved in this mechanism through the formation of calcium phosphate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations